A GPU based 3D raytracing algorithm for DUED laser fusion code - Savino, L; Schiavi, A; Atzeni, S (Plasma physics and controlled fusion, 2024)
These days, graphical processing units (GPUs) deliver performance comparable to that of hundreds of CPU cores. This level of performance allows certain classes of simulations to be run in-house on a standard consumer workstation, eliminating the need for a cluster. In this paper, it is shown that medium-resolution, 2D radiation hydrodynamics simulations for laser-driven inertial confinement fusion with realistic 3D laser raytracing can now be conducted on a single consumer device. A novel raytracing module has indeed been developed for the 2D Lagrangian radiation-hydro-nuclear code DUED (Atzeni 1986 Comput. Phys. Commun. 43 107–24; Atzeni et al 2005 Comput. Phys. Commun. 169 153–9) to leverage the computational power of GPUs. By employing 3D raytracing, more realistic investigations of laser-driven plasmas become feasible, with a particular focus on perturbations resulting from non-uniform laser irradiation.